PENGARUH KINERJA KEUANGAN DAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP NILAI PERUSAHAAN PADA BANK GO PUBLIC YANG TERDAFTAR DI BEI - Ardimas, Wahyu; Wardoyo, Wardoyo (Benefit: Jurnal Manajemen dan Bisnis, 2014)
The purpose of this study was to analyze the effect of corporate social responsibility (CSR) and financial performance on the firm value. The research object is the entire banking companies go public, amounting to 29 banks, but based on the completeness of the data it is only 22 banks sampled by the observation period 2008-2010. The independent variables are corporate performance (Return On Assets, Return on Equity, Operating Profit Margin, and Net profit Margin), and Corporate Responsibility Social, while the dependent variable is the firm value (Price Book Value). Data analysis consisted of multiple linear regression. The results of this study showed that the ROA and ROE have a significant effect on firm value, while OPM, NPM, CSR does not have a significant effect on firm value.